Mirage of fixed exchange rates. - OBSTFELD, Maurice (1995)
Puts forward some basic connections between monetary policy and exchange rate. Is of the view that a fixed exchange rate is very costly for a government to maintain, and suggests that efforts to reform monetary institutions should focus directly on restraining domestic inflation. The exchange rate should be used as an indicator but virtually never as the central target for monetary policy.